Barriers in implementing healthy eating among university students / Hamiza Hamdan and Nurhamiza Amira Shahrom - Hamdan, Hamiza; Shahrom, Nurhamiza Amira (Faculty of Hotel and Tourism, Universiti Teknologi MARA, 2017)
The purpose of this study is to explore the barriers in implementing healthy eating among university students. Unhealthy eating is one of the reasons that contributes to increasing of chronic diseases in the world. There are barriers that should be identified in implementing healthy eating practice. Therefore, this study was conducted in order to identify the barriers of implementing healthy eating practice among university students which is according to Malaysian Dietary Guidelines. This study was also conducted to seek for some solutions for these barriers. This study was conducted through qualitative method. The aim of using qualitative method was to provide the complete and detailed descriptions of what was being observed. Healthy eating consists of four elements which are individual factor, social factor, physical factor and media factor. These are the contributing factors that become the barriers for university students to practice healthy eating. However, this study only focused on Malaysian university students.